صُعُوبَاتُ تَعَلَّمِ الصَّرْفِ لَدَى طَلَبَةِ اللِّيسَانَس دِرَاسَةٌ تَحْلِيْلِيَّةٌ تَقْوِيمِيَّةٌ - راضية بوسته (My University, 2025)
Abstract: The study aimed to clarify the difficulties of learning morphology among Bachelor of Evaluation Analytical Study students.This is done by analyzing the answers of the study sample, which was represented by (111) university students distributed between the first and second years and (10) university professors at the University of Souk Ahras, where data and information were collected by questionnaire, and the descriptive analytical method was used through data analysis. The study reached a number of results, the most important of which is that morphology is important for mastering the classical Arabic language, as the difficulty of learning morphological rules is due to the teacher, the learn, and the subject of study. ---------------- الملخص: هدفت الدراسة إلى توضيح صعوبات تعلم الصرف لدى طلبة ليسانس-دراسة تحليلية تقويمية-؛ وذلك عن طريق تحليل إجابات عينة الدراسة التي تمثلت في (111) طالب جامعي موزع بين السنة الاولى والسنة الثانية و(10) أساتذة جامعيين بجامعة سوق أهراس، حيث تم جمع البيانات والمعلومات بواسطة الاستبيان، واستخدام المنهج الوصفي التحليلي من خلال تحليل البيانات . توصلت الدراسة إلى عدد من النتائج أهمها أنّ علم الصرف مهم لإجادة اللغة العربية الفصحى، حيث يرجع صعوبة تعلم القواعد الصرفية إلى المعلّم والمتعلم والمادّة الدّراسية . --------------- Résumé : L’étude visait à clarifier les difficultés d’apprentissage de la morphologie chez les étudiants en licence d’analyse d’évaluation. Elle a été réalisée en analysant les réponses de l’échantillon, composé de 111 étudiants universitaires répartis en première et deuxième année et de 10 professeurs de l’Université de Souk-Ahras. Les données et informations ont été collectées par questionnaire et analysées selon une méthode d’analyse descriptive. L’étude a abouti à plusieurs résultats, dont le plus important est l’importance de la morphologie pour la maîtrise de la langue arabe classique, car la difficulté d’apprentissage des règles morphologiques est liée à l’enseignant, à l’apprenant et au sujet étudié.
Keywords: Morphology; Learning Disabilities; Teaching Methods; علم الصرف، صعوبات التعلم، طرائق التدريس.: Morphologie; Troubles d’apprentissage; Méthodes d’enseignement